The viral aetiology of influenza-like illnesses in Kampala and Entebbe, Uganda, 2008 - Balinandi, Stephen (Afr J Lab Med, 2013)
BACKGROUND: As the threat of zoonoses and the emergence of pandemic-prone respiratory viruses increases, there is a need to establish baseline information on the incidence of endemic pathogens in countries worldwide. OBJECTIVES: To investigate the presence of viruses associated with influenza-like illnesses (ILI) in Uganda. METHODS: A cross-sectional study was conducted in which nasopharyngeal swab specimens were collected from patients diagnosed with ILI in Kampala and Entebbe between 14 August 2008 – 15 December 2008. A multiplex polymerase chain reaction assay for detecting 12 respiratory viruses was used. RESULTS: A total of 369 patients (52.3% females) was enrolled; the median age was 6 years (range 1–70). One or more respiratory viruses were detected in 172 (46.6%) cases and their prevalence were influenza A virus (19.2%), adenovirus (8.7%), human rhinovirus A (7.9%), coronavirus OC43 (4.3%), parainfluenza virus 1 (2.7%), parainfluenza virus 3 (2.7%), influenza B virus (2.2%), respiratory syncytial virus B (2.2%), human metapneumovirus (1.4%), respiratory syncytial virus A (1.1%), parainfluenza virus 2 (0.5%) and coronavirus 229E (0.5%). There were 24 (14.0%) mixed infections. CONCLUSIONS: This study identified some of the respiratory viruses associated with ILI in Uganda. The circulation of some of the viruses was previously unknown in the study population. These results are useful in order to guide future surveillance and case management strategies involving respiratory illnesses in Uganda.